Intron-Mediated Enhancement: A Tool for Heterologous Gene Expression in Plants? - Laxa, Miriam (Frontiers in Plant Science, 2017)
Many plant promoters were characterized and used for transgene expression in plants. Even though these promoters drive high levels of transgene expression in plants, the expression patterns are rarely constitutive but restricted to some tissues and developmental stages. In terms of crop improvement not only the enhancement of expression per se but, in particular, tissue-specific and spatial expression of genes plays an important role. Even though introns were used to boost expression in transgenic plants in the field of crop improvement for a long time, the mechanism behind this so called intron-mediated enhancement (IME) is still largely unknown. This review highlights the complexity of IME on the levels of its regulation and modes of action and gives an overview on IME methodology, examples in fundamental research and models of proposed mechanisms. In addition, the application of IME in heterologous gene expression is discussed.